Carvedilol pharmacokinetics and pharmacodynamics in relation to CYP2D6 and ADRB pharmacogenetics. (June 2011) - Sehrt, Daniel; Meineke, Ingolf; Tzvetkov, Mladen; Güültepe, Senol; Brockmööller, Jüürgen
Aims: Carvedilol is an effective treatment in hypertension and chronic heart failure. The medical impact of polymorphisms in CYP2D6 and in the ββ-adrenergic receptors ADRB1 and ADRB2 on the pharmacokinetics and pharmacodynamics of carvedilol is controversial.Methods: After carvedilol 25 mg was administered to 110 volunteers, concentrations were enantioselectively quantified and effects on resting and exercise-induced heart rate and blood pressure were analyzed using population pharmacokinetic, pharmacodynamic and pharmacogenetic modeling.Results: There were significant CYP2D6 allele-specific differences in carvedilol pharmacokinetics, but the CYP2D6 genotype had no effect on heart rate, blood pressure or adverse effects. ADRB1 Gly49 was associated with higher baseline heart rates and with greater carvedilol effects on exercise heart rates. Carriers of ADRB2 Gln27 had greater reduction in resting blood pressure by carvedilol compared with Glu27.Conclusion: Carvedilol is a drug where CYP2D6 -related pharmacokinetic variation is apparently not carried forward into pharmacodynamic variation. Although current knowledge does not allow utilizing ADRB1 and ADRB2 genotypes for clinical treatment decisions, our data should stimulate further research on the impact of these genotypes in health and disease. Original submitted 16 November 2010; Revision submitted 19 January 2011